Interaction Effects of Design Thinking-Based Learning and Adversity Quotient on Students’ Learning Independence and Creative Thinking Skills - Septian Dwi Cahyo; Hartono; Faisal; Firdaus Daud; Alimuddin Ali (Postgraduate, University of Mataram, 2026)
This study investigated the effect of Design Thinking-Based Learning (DTBL) on students’ learning independence and creative thinking skills based on adversity quotient (AQ). A quasi-experimental pretest–posttest control group design was employed involving 69 tenth-grade students of SMA Negeri 1 Sidrap. The experimental group was taught using DTBL, while the control group received Project-Based Learning (PjBL). Learning independence was measured using a self-regulated learning questionnaire, creative thinking skills were assessed using a Torrance-based creative thinking test, and AQ was measured using an adaptation of Stoltz’s Adversity Response Profile (ARP). Data were analyzed using descriptive statistics and factorial Analysis of Covariance (ANCOVA). The results showed that DTBL significantly affected learning independence (F = 4.602, p = 0.036) and creative thinking skills (F = 5.052, p = 0.028). The mean posttest score of learning independence in the DTBL class (M = 109.23) was higher than that of the PjBL class (M = 103.00), while the mean creative thinking score in the DTBL class (M = 61.74) also exceeded that of the PjBL class (M = 59.85). AQ significantly influenced learning independence (F = 9.222, p = 0.003), but not creative thinking skills (p = 0.279). A significant interaction between learning model and AQ was found on learning independence (p = 0.020), whereas no interaction effect was observed on creative thinking skills (p = 0.813). Therefore, DTBL was more effective than PjBL in improving students’ learning independence and creative thinking skills.